The Development of the Luyung Gymnastics Model in Rhythmic Gymnastics Learning Activities for Elementary School Students in Karangnongko District - Shabrina Bilqiss Nabilla; Dwi Gansar Santi Wijayanti; Agus Pujianto; Ipang Setiawan (Indonesian Journal for Physical Education and Sport, 2025)
The scope of physical education in independent curriculum includes games and sports, developmental activities, gymnastics activities, rhythmic activities, aquatic activities, extracurricular education, health, and others. Physical education in elementary school consists of three stages, namely Stage A consists of grades 1 and 2, Stage B consists of grades 3 and 4, and finally Stage C consists of grades 5 and 6. This research aims to develop gymnastics movements in rhythmic movement learning at the elementary school level. The development model used in this research is Research and Development (R&D) which is a research method used to produce products, and test the effectiveness of products. This research approach involves need analysis, model design, and evaluation. This research stage starts from initial observation with interview technique then continued with planning, product development, trial, revision to dissemination. The results of large-scale trials showed that the cognitive aspects of students obtained 82.91% which were included in the Very Good category. In the affective aspect, students obtained a presentation of 82.01% which was included in the Very Good category. And in the psychomotor aspect, students obtained a presentation rate of 82.21% which was included in the Very Good category. The result of this research is in the form of a "Luyung" gymnastics development product designed to increase students' interest in learning and become a reference for sports teachers to design rhythmic gymnastics movements that are more creative and efficient in improving the quality of learning.